Peningkatan Literasi Trading untuk Mendorong Konsistensi melalui Kegiatan Trading Bareng TPFx Surabaya - Sholihah, Siti Nurika Qori'atun; Rini, Hesty Prima (Universitas Pahlawan Tuanku Tambusai, 2026)
The growing interest in trading activities in Indonesia has not been fully matched by adequate financial literacy, potentially leading to undisciplined and speculative trading behavior, especially among novice traders. This community service activity aims to improve trading literacy and encourage consistent trading behavior through the Trading Bareng program organized by PT Trijaya Pratama Futures (TPFx) Surabaya. The method used is hands-on training, including an introduction to the company, real-time application of technical and fundamental analysis, and an emphasis on risk management. The results of the activity show an increase in participants' understanding of basic trading concepts, their ability to read market movements, and their awareness of the importance of discipline and risk management. This activity confirms that a practice-based educational approach is effective in shaping more consistent and sustainable trading patterns for novice traders.